1999
DOI: 10.1093/emboj/18.22.6211
|View full text |Cite
|
Sign up to set email alerts
|

Membrane raft microdomains mediate front–rear polarity in migrating cells

Abstract: The acquisition of spatial and functional asymmetry between the rear and the front of the cell is a necessary step for cell chemotaxis. Insulin-like growth factor-I (IGF-I) stimulation of the human adenocarcinoma MCF-7 induces a polarized phenotype characterized by asymmetrical CCR5 chemokine receptor redistribution to the leading cell edge. CCR5 associates with membrane raft microdomains, and its polarization parallels redistribution of raft molecules, including the raft-associated ganglioside GM1, glycosylph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
238
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(252 citation statements)
references
References 56 publications
12
238
2
Order By: Relevance
“…For instance, in HEK-293 cells, it was estimated that 11-18% of CCR5 was raft associated (Manes et al, 1999). Although CXCR4 was largely excluded from rafts, HIV binding induced lateral migration of CXCR4 to raft domains (Manes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in HEK-293 cells, it was estimated that 11-18% of CCR5 was raft associated (Manes et al, 1999). Although CXCR4 was largely excluded from rafts, HIV binding induced lateral migration of CXCR4 to raft domains (Manes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in HEK-293 cells, it was estimated that 11-18% of CCR5 was raft associated (Manes et al, 1999). Although CXCR4 was largely excluded from rafts, HIV binding induced lateral migration of CXCR4 to raft domains (Manes et al, 1999). A subsequent report showed that CXCR4 in PBLs and T cell lines was excluded from rafts irrespective of HIV binding (Kozak et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, ClC-3 and BK channels localize to the same cellular domains. Many membrane proteins are organized on cell membranes by lipid-raft domains and lipid rafts define front-rear cell polarity in MCF-7 adenocarcinoma cells (Manes et al, 1999). To see whether ClC-3 and BK channels are generally enhanced in lipid-raft domains, we also used a biochemical approach to separate these lipid domains.…”
Section: Clc-3 CL − Channels Colocalize With Bk K + Channels To Lipidmentioning
confidence: 99%
“…Treatment with cholesterol extracting agent disrupts both ligand binding to and signaling from CCR5, indicating that CCR5 activation depends on the integrity of lipid rafts [4]. T cells are rapidly polarized upon chemokine exposure [5] and this polarization is abrogated by disruption of lipid rafts [6]. Perhaps, in the context of CCR5, activation-induced signaling coordinates lipid raft aggregation, thereby facilitating immunological synapse formation.…”
Section: A Role For Chemokines In the Recruitment And Polarization Ofmentioning
confidence: 99%
“…GPCR-mediated transactivation of the epidermal growth factor [107] and the platelet-derived growth factor receptors [108] have been reported. Given that CCL5-CCR5 activation of Jurkat T cells correlates with the expression of CD3 [19], that CCR5 expression is associated with constitutive CD4 [9] expression and CCR5 localizes to lipid rafts upon ligand binding [4,6], activated CCR5 may function to recruit signaling intermediates of the TCR to potentiate (co)stimulation of T cells. CCL5 at micromolar doses can induce two distinct calcium fluxes in T cells: one dependent on G-proteins and the other on tyrosine kinases [15].…”
Section: Ccr Cross-talk With the Tcr Signaling Complexmentioning
confidence: 99%